Evaluation Of The New Students In Algerian University To Ensure The Quality Of Higher Education- Jijel University Model - Medini, Atmane; Yeghni, Samia (جامعة الوادي - University of Eloued, 2021)
Quality assurance is a major challenge for higher education and in response to the requirements of the economic sectors in Algeria as in the rest of the world, as this concept has become a topical issue in all Algerian universities. Where the aim of the study was to know the effect of newcomer learning on the quality of the results. She relied on the Algerian university study via Jijel model. . She concluded that the student suffers from a weakness in acquiring technical knowledge and recommends the need to have a strategy to enable students to master technical knowledge.
مقال
Keywords: quality assurance ; students ; learning ; Jijel University